The role of the english language in the medical field - Rusova, M. O. (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the abstract is to highlight the importance of the English language in the global world picture and to concentrate on its impact on the study process in terms of the medical field.
Keywords: тези доповідей